2012
DOI: 10.1017/s0007485312000168
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of three chemosensory proteins from Spodoptera exigua and effects of gene silencing on female survival and reproduction

Abstract: Insect chemosensory proteins (CSPs) are supposed to transport hydrophobic chemicals to receptors on sensory neurons. However, CSPs are broadly expressed in various insect tissues, suggesting their involvement in the physiological processes beyond chemoreception. So, the exact physiological roles of CSPs in insects still need to be unraveled. In this study, three full-length of CSP genes from Spodoptera exigua have been cloned and characterized. The deduced amino acid sequences of SexiCSP1, SexiCSP2 and SexiCSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 34 publications
3
56
0
Order By: Relevance
“…Interestingly, while most of the OBPs expression was not visible when entire animals were used for RNA extraction (transcript “dilution”), many CSP transcripts could still be highly visible in different samples, suggesting that their expression is not restricted to the olfactory organs. This correlates well with some evidences that CSP function would not be restricted to olfaction [38, 39] and that these proteins would act in fact as general carriers of hydrophobic molecules throughout the insect body. Interestingly, the expression of some ORs was not restricted to the olfactory organs and several could be observed as expressed in the fat body or the midgut (Figure 6A).…”
Section: Resultssupporting
confidence: 89%
“…Interestingly, while most of the OBPs expression was not visible when entire animals were used for RNA extraction (transcript “dilution”), many CSP transcripts could still be highly visible in different samples, suggesting that their expression is not restricted to the olfactory organs. This correlates well with some evidences that CSP function would not be restricted to olfaction [38, 39] and that these proteins would act in fact as general carriers of hydrophobic molecules throughout the insect body. Interestingly, the expression of some ORs was not restricted to the olfactory organs and several could be observed as expressed in the fat body or the midgut (Figure 6A).…”
Section: Resultssupporting
confidence: 89%
“…Compared to the AlOBP genes highly expressed in the antennae, only three AlCSP s had antennae-biased expression, indicating that these three genes may be involved in the recognition and transmission of sex pheromones, host volatiles, and other odorants. On the other hand, many insect CSPs are broadly expressed in non-chemosensory tissues and have non-chemosensory functions, such as SexiCSP3, which has been shown to have effects on the survival and reproduction of S. exigua (Gong et al, 2012), and AmelCSP5, which is involved in embryonic integument formation in A. mellifera (Foret, Wanner & Maleszka, 2007). In this study, many AlCSP s were found in various tissues and were highly expressed in non-chemosensory tissues suggesting that these AlCSPs (especially AlCSP14, which had the highest expression) may be involved in other physiological functions apart from chemosensory ones.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike OBPs, CSPs are smaller and more conserved in distinct insects, which only have four conserved cysteines that form two interlocking disulphide bridges (Bohbot et al, 1998; Lartigue et al, 2002; Maleszka & Stange, 1997; Pelosi, Calvello & Ban, 2005; Zhang et al, 2014). Furthermore, OBPs are usually specifically or predominately expressed in the antennae, whereas many CSPs are expressed in the antennae and other tissues (Pelosi, Calvello & Ban, 2005; Vogt, 2005; Zhang et al, 2016a; Zhang et al, 2013), suggesting insect CSPs have both chemosensation and non-chemosensation functions as is illustrated by their association with chemosensation in moths (Jacquin-Joly et al, 2001; Sun et al, 2015; Zhang et al, 2014), limb regeneration in Periplaneta eparate (Nomura et al, 1992), embryo development in Apis mellifera (Maleszka et al, 2007), behavioral phase change in Locusta migratoria (Guo et al, 2011), and female moth survival and reproduction in Spodoptera exigua (Gong et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…A number of other genes in moths have also been studied by using RNAi techniques, such as the chemosensory protein from S. exigua [121], the CO 2 gustatory receptor from H. armigera [122], the delta 6-desaturase which is the rate-limiting factor in the biosynthesis of polyunsaturated fatty acids in B. mori [123], the serotonin receptor B that relates to diapause initiation in A. pernyi [46], and the aspartate decarboxylase which is required for normal pupa pigmentation in B. mori [124]. …”
Section: Use Of Rnai For Gene Function Analysis In Mothsmentioning
confidence: 99%